2008
DOI: 10.1021/la801730u
|View full text |Cite
|
Sign up to set email alerts
|

Delamination of Surfactant-Intercalated Brucite-Like Hydroxy Salts of Cobalt and Copper and Solvothermal Decomposition of the Resultant Colloidal Dispersions

Abstract: Surfactant anion intercalated hydroxy salts of copper and cobalt of the formula M(OH)2- x (surf)x.mH2O [M = Cu, Co; surf = dodecyl sulfate, dodecyl benzene sulfonate, and x = 0.5 for Cu and 0.67 for Co] delaminate readily in 1-butanol to give translucent colloidal dispersions that are stable for months. The extent of delamination and the colloidal dispersion observed in these solids is higher than what had been observed for layered double hydroxides. The dispersions yield the corresponding nanoparticulate oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Exfoliation of layered solids has been exploited as a route to nanomaterials [1][2][3] and functional nanocomposites [4][5][6][7][8][9][10]. Exfoliation of layered solids results in colloidal suspensions of solvated monolayers or packets of few layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exfoliation of layered solids has been exploited as a route to nanomaterials [1][2][3] and functional nanocomposites [4][5][6][7][8][9][10]. Exfoliation of layered solids results in colloidal suspensions of solvated monolayers or packets of few layers.…”
Section: Introductionmentioning
confidence: 99%
“…The b-form is of the formula M(OH) 2 behavior [29,30]. We have reported the exfoliation behavior of surfactant intercalated a-hydroxides of nickel and cobalt in organic solvents like butanol [29].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained pillared LDHs materials have been used in chromatography, chemical or biosensors, precursors for magnetic materials, and catalysis, etc. [9][10][11][12]. But up to now, the intercalated guest species mainly focus on inorganic anions, anionic polymers, organic molecules, and others [13][14][15], the research report on the intercalation of semiconducting guest species such as TiO 2 and MnO 2 into the interlayer of LDHs host layers is few, which greatly restricts their application, in particular in the electronic, magnetic and optical application field [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrotalcite, like anionic clays or more generally speaking layered double hydroxides (LDHs), show the ability of LDHs to allow cells to grow well and to function properly or even to force living cells to make changes according to the nature of the particular biomolecules [11,12]. The LDH clay matrix is also able to bring into a cumulative structure not only the advantage of good biocompatibility and controlled textural features [13,14] but also high adsorption and ion exchange capacities [15]. It was also reported that the particular texture of the LDH allows bacteria and viruses to adsorb on the clay matrix [12] and thus to interact closely with the supported nanoparticles.…”
Section: Introductionmentioning
confidence: 99%